2020
DOI: 10.1002/acr.24131
|View full text |Cite|
|
Sign up to set email alerts
|

2019 American College of Rheumatology/Arthritis Foundation Guideline for the Management of Osteoarthritis of the Hand, Hip, and Knee

Abstract: Objective To develop an evidence‐based guideline for the comprehensive management of osteoarthritis (OA) as a collaboration between the American College of Rheumatology (ACR) and the Arthritis Foundation, updating the 2012 ACR recommendations for the management of hand, hip, and knee OA. Methods We identified clinically relevant population, intervention, comparator, outcomes questions and critical outcomes in OA. A Literature Review Team performed a systematic literature review to summarize evidence supporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
1,153
1
59

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,403 publications
(1,225 citation statements)
references
References 40 publications
12
1,153
1
59
Order By: Relevance
“…In a Cochrane review of 54 randomized controlled trials of land-based exercise for knee osteoarthritis, exercise has shown to reduce pain, improve physical function and quality of life immediately after treatment (31) and the 2019 American College of Rheumatology osteoarthritis guidelines strongly recommended exercise as a treatment for osteoarthritis (32). Interestingly, a study of 126 participants with knee OA and at least one morbidity found that a 20-week individualized, comorbidity adapted land-based exercise program resulted in improvement in WOMAC physical function score of 7.43 (33) while our study of 4-8 weeks of water exercise intervention saw a similar effect (WOMAC physical function score improvement of 7.6) with a much shorter intervention time.…”
Section: Discussionmentioning
confidence: 99%
“…In a Cochrane review of 54 randomized controlled trials of land-based exercise for knee osteoarthritis, exercise has shown to reduce pain, improve physical function and quality of life immediately after treatment (31) and the 2019 American College of Rheumatology osteoarthritis guidelines strongly recommended exercise as a treatment for osteoarthritis (32). Interestingly, a study of 126 participants with knee OA and at least one morbidity found that a 20-week individualized, comorbidity adapted land-based exercise program resulted in improvement in WOMAC physical function score of 7.43 (33) while our study of 4-8 weeks of water exercise intervention saw a similar effect (WOMAC physical function score improvement of 7.6) with a much shorter intervention time.…”
Section: Discussionmentioning
confidence: 99%
“…(54,55) Other limitations include specialty societies and payers in making recommendations for ultrasound treatment of knee OA or lack thereof. (8,(56)(57)(58) Unfortunately, some payer coverage and utilization policies have not been updated for over 10 years, failing to account for recent, high quality evidence in establishing coverage determinations. (13,14,58) Additionally, there appears to be an issue with the use of o ce-based ultrasound devices causing harm (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…(67) Costs used in the analysis were based off accepted treatment guidelines as identi ed by the American College of Rheumatology and were not prospectively captured. 8 As well, costs were assumed to be national averages and thus would vary by region of the country.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Financial incentives for KA implantation and surgery plannability as well as a limited budget for the prescription of exercise therapy are mentioned (9). It has also been discussed that some patients and some physicians have negative attitudes towards conservative osteoarthritis treatment despite many guidelines with consistent evidence-based recommendations for exercise therapy, self-management programmes and weight loss in overweight patients (11,28,29). They consider osteoarthritis as fateful and later surgery as inevitable (30).…”
Section: Discussionmentioning
confidence: 99%